Kontribusi Kekuatan Otot Lengan, Kekuatan Otot Perut, Dan Kekuatan Otot Tungkai Terhadap Kecepatan Renang Gaya Kupu-Kupu - Sahabuddin Sahabuddin; Hikmad Hakim; Sudirman Sudirman; Suriah Hanafi (Jurnal Speed (Sport, Physical Education, Empowerment), 2022)
This study aims to determine the contribution of arm muscle strength, abdominal muscle strength, and leg muscle strength to butterfly stroke swimming speed. This research includes the type of descriptive research. The population of this study were all Paotere Swimming Athletes in Makassar City with a total sample of 30 people selected by random sampling. The data analysis technique used is the correlation analysis technique using the SPSS Version 22.00 system at a significant level of 95% or a0,05. Based on data analysis with statistical calculations and the results of hypothesis testing as well as from the discussion, the results of this study are concluded as follows: (1) arm muscle strength contributes to butterfly stroke swimming speed of 39.5%; (2) abdominal muscle strength contributes 25.5% to butterfly stroke swimming speed; (3) leg muscle strength against butterfly stroke swimming speed of 48.6%; and (4) arm muscle strength, abdominal muscle strength and leg muscle strength contribute 63.5% to butterfly stroke swimming speed.